5.7k views
17 votes
2 (3x - 5) + 4 = -18


Solve for 20 Points

User Mbrt
by
4.4k points

2 Answers

7 votes

Answer:

x=-2

Explanation:

2(3x-5)+4=-18

We move all terms to the left:

2(3x-5)+4-(-18)=0

We add all the numbers together, and all the variables

2(3x-5)+22=0

We multiply parentheses

6x-10+22=0

We add all the numbers together, and all the variables

6x+12=0

We move all terms containing x to the left, all other terms to the right

6x=-12

x=-12/6

x=-2

User PSKP
by
4.9k points
4 votes

Answer:

x = -2

Explanation:

2(3x - 5) + 4 = -18

Distribute the 2

6x - 10 + 4 = -18

6x - 6 = -18

Add 6 to both sides

6x = -12

Divide both sides by 6

x = -2

Check:

2(3x - 5) + 4 = -18

substitute x = -2 into the original equation

2(3(-2) - 5) + 4 = -18

2(-6 - 5) + 4 = -18

2(-11) + 4 = -18

-22 + 4 = -18

-18 = -18

So x = -2 is true.

User Sekm
by
5.3k points